Chk2 prevents mitotic exit when the majority of kinetochores are unattached - Petsalaki, Eleni (The Rockefeller University Press, 2014)
The spindle checkpoint delays exit from mitosis in cells with spindle defects. In this paper, we show that Chk2 is required to delay anaphase onset when microtubules are completely depolymerized but not in the presence of relatively few unattached kinetochores. Mitotic exit in Chk2-deficient cells correlates with reduced levels of Mps1 protein and increased Cdk1–tyrosine 15 inhibitory phosphorylation. Chk2 localizes to kinetochores and is also required for Aurora B–serine 331 phosphorylation in nocodazole or unperturbed early prometaphase. Serine 331 phosphorylation contributed to prometaphase accumulation in nocodazole after partial Mps1 inhibition and was required for spindle checkpoint establishment at the beginning of mitosis. In addition, expression of a phosphomimetic S331E mutant Aurora B rescued chromosome alignment or segregation in Chk2-deficient cells. We propose that Chk2 stabilizes Mps1 and phosphorylates Aurora B–serine 331 to prevent mitotic exit when most kinetochores are unattached. These results highlight mechanisms of an essential function of Chk2 in mitosis.